Public management at the bargaining table - Warner, Kenneth O.; Hennessy, Mary L. (Chicago : Public Personnel Association, 1967)
This book carries forward the series of related monographs on government labor relations published by the Public Personnel Association. Monograph one, Management Relations with Organized Public Employees: Theory, Policies and Programs, published in 1963. Monograph two, Developments in Public Employee Relations: Legislative, Judicial, Administrative, published in 1965, examined in some depth the more important aspects of management's relations with organized employees. Monograph three, Collective Bargaining in the Public Service: Theory and Practice, published in 1967, extended the coverage of this subject matter to Canadian jurisdictions. Monograph four, Public Management at the Bargaining Table, pursues the subject a step further.
Includes index.
Includes bibliographical references: p. 435-474.
rpm 14/03/2018
Loans
Keywords: Collective bargaining; Employee-management relations in government